AIDS, poverty, and hunger: Challenges and responses - Gillespie, Stuart (International Food Policy Research Institute, 2006)
More than a quarter-century after HIV was identified, the long-wave, intergenerational nature of AIDS epidemics is becoming starkly evident. We may have passed the peak of the infection wave in many countries, but the multiple impact waves continue to gather momentum. Advances are indeed being made in prevention, treatment, care, and support. Yet, in 2006 in many of the hardest-hit countries, fewer than one in eight people living with HIV have sustained access to lifesaving drugs. At the same time, we are learning more about the intertwining of HIV and AIDS with poverty, nutrition, and agriculture. It is now clear that, if the Millennium Development Goals on hunger and AIDS are to be met, especially in eastern and southern Africa, we need to continue to research these dynamics and proactively address them through better, AIDS-responsive food policy and programming. Against this backdrop, the International Food Policy Research Institute convened the International Conference on HIV/AIDS and Food and Nutrition Security: From Evidence to Action in Durban, South Africa, April 14-16, 2005. ... As highlights from the conference, the chapters in this book amply illustrate the diversity of activity and the imperative for interdisciplinary work in this new field. Economists, nutritionists, anthropologists, health specialists, and other development professionals have approached the issue from different angles, often using innovative methods, to generate important new findings.